2020
DOI: 10.1152/ajpendo.00425.2019
|View full text |Cite
|
Sign up to set email alerts
|

Pasteurized Akkermansia muciniphila protects from fat mass gain but not from bone loss

Abstract: Probiotic bacteria can protect from ovariectomy (ovx)-induced bone loss in mice. Akkermansia muciniphila is considered to have probiotic potential due to its beneficial effect on obesity and insulin resistance. The purpose of the present study was to determine if treatment with pasteurized Akkermansia muciniphila (p Akk) could prevent ovx-induced bone loss. Mice were treated with vehicle or p Akk for 4 wk, starting 3 days before ovx or sham surgery. Treatment with p Akk reduced fat mass accumulation confirming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 50 publications
0
27
0
1
Order By: Relevance
“…As shown in Figure S5A,B in the Supporting Information, pasteurization caused 100% death of Akk and entirely blocked the secretion of EVs by Akk , suggesting that the failure of pasteurized Akk to induce bone‐protective effects in study by Lawenius et al. [ 27 ] may be associated with the impairment of production of Akk ‐EVs.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As shown in Figure S5A,B in the Supporting Information, pasteurization caused 100% death of Akk and entirely blocked the secretion of EVs by Akk , suggesting that the failure of pasteurized Akk to induce bone‐protective effects in study by Lawenius et al. [ 27 ] may be associated with the impairment of production of Akk ‐EVs.…”
Section: Resultsmentioning
confidence: 98%
“…The first reason is likely that the process of pasteurization causes Akk death and impairs the production of functional Akk ‐EVs. The negative effect of pasteurized Akk on bone mass in normal mice [ 27 ] may be due to that the death of Akk results in the generation of some substances detrimental to bone, which still needs future investigation. Second, the difference in the frequency of Akk treatment may also lead to two opposite outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there is little or no evidence that this species is present the adult cow rumen while the genus Akkermansia has been reported to exist in the gastrointestinal tract of goats and camels 37,38 . A. muciniphila is a mucin degrader and an abundant member of the human gut microbiome [39][40][41][42] . The transition from the first to the second month of life was followed by an increase in members of the Firmicutes phylum, which was mainly attributed to the Lachnospiraceae family ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, even when A. muciniphila is killed through pasteurization, supplementation demonstrated beneficial effects by protecting from ovariectomy-induced fat mass gain (72). In overweight insulin-resistant humans, a randomized, doubleblind, placebo-controlled pilot study showed that daily oral supplementation of 10 10 live or pasteurized A. muciniphila bacteria for 3 months was safe and well tolerated, and improved insulin sensitivity, reduced insulinemia, plasma total cholesterol, body weight, fat mass and hip circumference, without great changes in the overall gut microbiota composition (43).…”
Section: Supplementation Of a Muciniphila In The Context Of Metabolimentioning
confidence: 99%